Changes in quality characteristics of pomegranate juice concentrate during refrigerated storage - Muzaffar, Khalid; Nayik, Gulzar Ahmad; Gull, Amir; Kumar, Pradyuman (Journal of Postharvest Technology, 2017)
The present study was carried out to determine the changes in various quality characteristics of pomegranate juice concentrate at refrigerated storage (4°C). Effect of refrigerated storage on anthocyanin, ascorbic acid, total phenolic content and antioxidant activity of pomegranate juice concentrate was determined for 42 days of storage period after every 7 days of time interval. During the refrigerated storage, anthocyanin content, ascorbic acid content, total phenolic content and antioxidant activity decreased as storage time increased. Ascorbic acid showed higher reduction percentage (90.29%) during the storage. For lower storage period, reduction in anthocyanin content, total phenolic content and antioxidant activity was non-significant (p < 0.05), however significant reduction was observed for prolonged storage period.